"Molecular analysis of the rare S–s– red blood cell phenotype in blood donors and patients in south‐east Brazil". Issue 3 (19th February 2019) - Santos, Flávia Leite Souza; Cuter, Talitha Baldin; Rodrigues, Evandra Strazza; Bettarello, Êmile Cristina; Ubiali, Eugenia Maria Amorim; Castilho, Lilian Maria; Kashima, Simone; Covas, Dimas Tadeu
Abstract : Background and objectives: The rare S–s– phenotype has two main molecular backgrounds. GYPB deletions give rise to the S–s–U– phenotype, which loses the expression of the U antigen, while variant GYPB alleles usually lead to the S–s–U +var phenotype, which express a variant U antigen. The S–s– phenotype is typically found in people of African origin and represents a challenge in transfusion sets, especially when S–s– patients develop anti‐U. Molecular analysis is the most reliable method for determining U antigen status. We studied the molecular basis of the S–s– phenotype in donors and patients at Regional Blood Center of Ribeirão Preto. Material and Methods: Five patients and 25 donors with the S–s– phenotype were investigated through real‐time PCR for the GYPB*S/s polymorphism, followed by an allele‐specific/RFLP‐PCR for GYPB deletion ( GYPB*Null ) and for its main variants: GYPB*P2 and GYPB*NY . DNA sequencing was conducted in one sample. Results: Two samples were heterozygous GYPB*P2/GYPB*NY, eight were homozygous/hemizygous for GYPB*P2 and 19 samples were homozygous for GYPB*Null . A hybrid gene ( GYPB‐E‐B.Ros ) was found in one sample after discrepant results in the initial tests. Conclusion: GYPB deletion is the main mechanism responsible for the S–s– phenotype in our donors and patients. It is essential to evaluate the main GYPB variant alleles when genotyping in order to obtain the correct prediction of the phenotype. Hybrid genes lead to discrepancies between genotype and phenotype and may not be detected by conventional molecular assays.